What drives the demand for temporary agency workers? - Elke J. Jahn; Jan Bentzen (Institute for the Study of Labor (IZA), 2010)
Temporary agency employment has grown steadily in most European countries over the past three decades as part of the general trend towards increased employment flexibility. Yet to this day, it remains an open question what drives the demand for temporary agency workers. The paper examines, first, whether the deregulation of temporary agency employment is responsible for the growth of the flexible staffing industry. Second, we investigate the cyclical behavior of temporary agency employment. Using monthly data for Germany covering the period 1973-2008, we show that the continuous liberalization of this sector is not responsible for the surge in temporary agency employment. Our analysis reveals, moreover, that temporary agency employment exhibits strong cyclical behavior and correlates with main economic indicators in real time. Since most European countries promoted the use of temporary agency employment in a similar way, we believe that our results may be interesting from an international perspective as well.
Keywords: C41; J23; J40; J48; K31; 330; temporary agency employment; regulation; labor law; business cycle